Peculiarities of teachers’ inferiority feeling and experienced stress - Kepalaitė, Albina (Social Welfare: Interdisciplinary Approach, 2015)
The presented research deals with peculiarities of links between the feeling of inferiority and stress among teachers. Significant distribution of inferiority feeling indicators with regard to age and years of service was identified. Distribution of stress indicators with regard to age is significant. The disclosed significant link between the feeling of inferiority and stress indicators can be explained by mutual interaction: the feeling of inferiority can serve as a source of stress for teachers and, in turn, experienced stress could enhance the natural feeling of inferiority, which is inherent to all.
Keywords: self-esteem; the feeling of inferiority; stress